Household Fuel Preference and Its Association with Breathing Difficulty among Rural Women in Jodhpur, Rajasthan: A Cross-sectional Study - Neeti Rustagi; Shaima Abdul Jabbar; R. Ranjitha; Arun Kumar Sharma; Suman Saurabh; Ankit Mittal (Indian Journal of Public Health)
Background: Indoor air pollution is a critical global health concern and is associated with an increased incidence of respiratory infections. Despite the introduction of a subsidiary scheme, the adoption of clean fuel remains limited in rural India. Objectives: The current study investigated the fuel preferences and its association with participants characteristics, particulate matter (PM2.5) levels and respiratory complaints. Materials and Methods: A cross sectional study was done among rural women in Jodhpur, Rajasthan. A total of 480 women aged 15 years and above were included, and 120 households were selected using systematic random sampling technique for PM2.5 level assessment. Statistical analysis was done using Chi-square test, Fischer’s exact test, Mann–Whitney U test and Kruskal–Wallis test. Post hoc test with Bonferroni correction were used to identify differences between groups of fuel users. Results: The study revealed that 43.1% (207 participants) primarily used biomass as their fuel of choice, while 32.5% (156) primarily preferred liquified petroleum gas (LPG). Only LPG was used by 19.7% (95) of participants, and a small proportion of 4.58% (22) relied solely on mud stoves. There was significant association between education status, family income, years of cooking and fuel preferences among the participants (P < 0.05). The PM2.5 levels were higher among biomass users than LPG users. Conclusion: Study highlighted the intricate interplay between sociodemographic factors, cooking practices, PM2.5 concentration, and respiratory symptoms in rural settings, emphasizing the need for increased advocacy on LPG adoption to mitigate indoor air pollution-related health risks.